Feasibility of Fe3O4 nanoparticles decorated reduced graphene oxide heterostructure as photocatalyst and chemical sensors / Teo Peik See - Teo, Peik See (2015)

(untitled)
In this study, iron oxide/reduced graphene oxide (Fe3O4/rGO) nanocomposite materials were successfully synthesized via a simple, eco-friendly and cost-effective approach at room temperature. The XRD spectra indicated peaks that attributed to the face-centre-cubic phase Fe3O4, while the absence peak of GO in nanocomposite provides evidence for the reduction of GO. The field emission scanning electron microscopic (FESEM) images showed Fe3O4 nanoparticles were uniformly deposited on the rGO sheets with a narrow size distribution for all the nanocomposites. Besides, the synthesized Fe3O4/rGO nanocomposites were found to be superparamagnetic in nature at room temperature. In the photocatalysis application, methylene blue (MB) solution was used as a model organic pollutant; the Fe3O4/rGO nanocomposite materials showed better adsorption and excellent photocatalytic activity towards the degradation of MB under natural sunlight irradiation due to the synergistic effect that arises between rGO and Fe3O4 nanoparticles. Interestingly, a maximum photodegradation of almost 100% MB were achieved at 1 h light irradiation. Moreover, the magnetically separable Fe3O4/rGO nanocomposite exhibit good sustainability and photocatalytically stable morphology even after eight cycles of photocatalytic treatment. Thus, this newly prepared Fe3O4/rGO nanocomposite could serve as potential candidate in variety environmental remediation. The electrochemical studies were carried out with the iron oxide/graphene modified glassy carbon electrode (Fe3O4/rGO/GCE) for the simultaneous detection of dopamine (DA) and ascorbic acid (AA). The detection limit (S/N=3) was found to be 0.42 μM and 0.12 μM for AA and DA, respectively. The Fe3O4/rGO/GCE displayed not only excellent electrocatalytic activity and remarkable electron transfer kinetics towards the oxidation of DA but also portrayed capability of high sensitivity and selectivity toward simultaneous detection of AA and DA. In a nutshell, the Fe3O4/rGO/GCE has iv been proved as a promising candidate and applicable for electrocatalysis and chemical sensor applications